Concentrations and Toxic Implications of Dioxin‐Like Polychlorinated Biphenyls in Soil Samples from Electrical Power Stations in Lagos, Nigeria. (25th January 2022) - Folarin, Bilikis T.; Abdallah, Mohamed; Oluseyi, Temilola O.; Harrad, Stuart; Olayinka, Kehinde O.
Abstract: Dioxin‐like polychlorinated biphenyls (dl‐PCBs) are ubiquitous chemicals which mediate toxicity in a way similar to polychlorinated dibenzo‐ p ‐dioxins and polychlorinated dibenzofurans. In silico modeling was used to predict the absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties of eight dioxin‐like PCBs in soil samples of 12 power stations in Lagos, Nigeria. Concentrations of Σdl‐PCB8 in soil samples ranged from 490 to 61, 000 pg g −1, with mean concentrations of 17, 000 pg g −1 . The corresponding toxic equivalent (TEQ) concentrations of Ʃdl‐PCB8 ranged from 0.01 to 450 pg TEQ g −1, with a mean value of 42 pg TEQ g −1 . Mean TEQ concentrations for Ʃdl‐PCB8 in soil samples from all but one of the sites exceeded the Canadian guideline value of 4 pg TEQ g −1 and the US and German guideline values of 5–10 pg TEQ g −1 . However, the TEQ concentrations obtained were all below the US action level of 1000 pg TEQ g −1 . The ADMET predictions revealed that all studied dl‐PCBs are inhibitors of three major isoforms (1A2, 2C9, and 2C19) of cytochrome P450 enzyme. Acute oral toxicity (median lethal dose) predictions revealed that all target dl‐PCBs were class III compounds. Hepatotoxicity and carcinogenicity were positive, signifying that the studied compounds all have a tendency to elicit these effects. Occupational daily TEQ exposure via soil ingestion was estimated for an average adult worker weighing 70 kg. The maximum exposure obtained was 0.14 pg TEQ kg −1  body weight day −1, which is half of the European Food Safety Authority (EFSA) tolerable daily intake (TDI) for dioxin‐like compounds. This raises concern over the possible exceedance of the EFSA TDI for these workers if other dietary and nondietary exposure pathways and dioxin‐like compounds are considered. Environ Toxicol Chem 2022;41:800–809. © 2021 SETAC